Panax ginseng C.A. meyer alleviates benign prostatic hyperplasia while preventing finasteride-induced side effects - Park, Ja Yeon; Park, Woo Yong; Song, Gahee; Jung, Se Jin; Kim, Beomsu; Choi, Minji; Kim, Sang Hee; Park, Jinbong; Kwak, Hyun Jeong; Ahn, Kwang Seok; Lee, Jun Hee; Um, Jae-Young (Frontiers in Pharmacology, 2023)
Panax ginseng C.A. Meyer is already a well-known medicinal plant. It has a variety of beneficial effects on such as immune function, male erectile dysfunction, cancer, excessive oxidants, and aging issues. In this study, we aimed to verify the therapeutic effects of a water extract of P. ginseng (PGWE) on benign prostatic hyperplasia (BPH) in testosterone propionate (TP)-induced BPH rats and TP-treated RWPE-1 human epithelial cells. In the TP-induced BPH rat model, PGWE alleviated the pathological markers of BPH such as weight and epithelial thickness of the prostate, and the serum level of dihydrotestosterone. PGWE downregulated androgen-related BPH factors such as 5-reductase 2 and androgen receptor. PGWE also upregulated Bax, which is an initial factor of apoptosis, while increasing mitochondrial dynamics in both in vivo and in vitro BPH models. Furthermore, PGWE not only showed an effect like that of finasteride (Fi), but also protected against Fi-induced sperm loss when PGWE was administered in combination with Fi without compromising the therapeutic effects of Fi on BPH. These findings suggest that PGWE could be an alternative therapeutic agent for BPH.